The survival of broods of the Egyptian Goose in Uganda - Eltringham, S K (Wildfowl, 1974)
Details of sixty-two broods of the Egyptian Goose Alopochen aegyptiacus on a hippo wallow in western Uganda were collected over a 4-year period between 1968 and 1972. Fourteen pairs used the wallow regularly while a few other pairs appeared sporadically. The average size of the broods when first seen was 6.5 with a range of 1 to 17. Of the goslings, 60.4% survived for a period of 60 days or more after first sighting but there were significant differences between the survival in certain years. Mortality was greatest in the first 25 days. There was no significant correlation between survival and brood size. A greater number of broods appeared on the wallow during the wet seasons than during the dry but there was little seasonal variation in the number of young reared to the 60-day stage except that very few, if any, young were produced in the first 3 months of the year. Some pairs were more successful than others in producing or rearing young. Possible mortality factors are discussed and it is concluded that avian predators are probably responsible for many deaths.